Introductory study of weeds with developing Taif Rosa crops in Al-Hada and Al-Shafa Area - Mohammad Moneruzzaman, Khandaker; Majrshi A., A (2016)
Background: The present study was conducted to explore the weed flora in Rosa crop fields of Al-Hada and Al-Shafa region of Saudi Arabia. The weeds are developing wild plants grow in different areas without the human will or desire than the consequences of this growth, different things, including what is positive and some are negative. Weeds are common in many landscape situations including around rose and other ornamental flowering plants. Taif rosa plant commercially cultivated in Al- Hada and Al- Shafa region of Saudi Arabia. The aim of this study was identify the common weeds of Taif Rosa plant growing in some of the region of Al- Hada and Al- Shafa. Results: The results showed that the existence of a vital diversity to a group of developing weeds, where were identified more than 5000 species of weeds that belong to the family 15, and 45 species of weeds. Conclusion: This study has shown that the most prevalent of the weed family: Brassicaceae and the most widespread weed is Brassica tournefortii. This study have great significant value to develop Taif rose industry.